DURATION AND EXTENT OF ADIPOCERE FORMATION IN HOT- HUMID AREAS OF PAKISTAN: A RETROSPECTIVE STUDY - Khan, Shaukat Ali; Malik, Romana; Hammad, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To find out duration of adipocere formation in hot and humid area. Study Design: Cross sectional study. Place and Duration of Study: Mohi-Ud-Din Islamic Medical College Mirpur Azad Kashmir and HITEC-IMS Taxila, from Jan 2017 to Jan 2019. Methodology: Total 25 cases with adipocere formation were included in this study. The cause of death, time since death, death circumstances, surrounding environment from where the body was recovered and demographic profile of the deceased were considered, while cases of septicemic deaths were excluded from the study. The adipocere was confirmed by forensic medicine consultants by its soft, moist and greasy consistency, grayish white appearance and ammoniacal smell. Results: Most of the cases recovered during months of March to June from open and closed areas, while 3 cases were recovered from water source or river banks. The time duration of recovery from time of death was from 5 days to 15 days 3h. The adipocere formation showed a high odds ratio 2.0-(95%-CI-0.115-3.482) and OR-1.5-(95%-CI-.098-2.306) for bodies recovered from water and open areas respectively. The adipocere formation in hot and rainy season showed OR-3.3-(95%-CI .190-4.199) and OR-2.4-(95%-CI .122-3.642) respectively. The adipocere formation occurred more during days 1-5 with an OR-1.9-(95%-CI .221-1.625). Conclusion: The adipocere formation can be seen as early as 2 days in a hot humid environmentin closed areas, while the extent of adipocere is larger in bodies recover from water source.